Pelaksanaan Pelayanan Sayang Warga Sebagai Wujud Pengabdian Kepada Masyarakat di Balai RW Kelurahan Rungkut Kidul Kota Surabaya - Rindyi Putri Lestari; Sishadiyati (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Population administration is a series of activities carried out to organize and regulate population documents and data. The Surabaya City Government, through the Surabaya City Population and Civil Registration Service, has created a service innovation, namely the Citizens' Love Service, which is carried out at the nearest RW Hall with the aim of increasing the efficiency and effectiveness of services because the population administration process is carried out closer to the community. This program runs with the help of sub-district officers who provide services at the RW Hall. The methods used to create a society with orderly population administration are direct observation in the field, outreach, interviews and document study to complete the required data. Through this MSIB program, the author, as an intern, hopes to help the Surabaya city government in improving the quality of public services by participating in the Dear Citizens service program in Rungkut Kidul Village.